1995
DOI: 10.1037/0096-1523.21.5.1199
|View full text |Cite
|
Sign up to set email alerts
|

Priming and response selection processes in letter classification and identification tasks.

Abstract: The processing of isolated visual letters was studied by means of a priming paradigm. In alphabetic (letter vs. nonletter) classification, any letter prime reduced response times to letter targets. Additional facilitation occurred only with primes physically identical to the target. In letter naming, facilitation was seen with primes nominally identical to the target even when they were physically different. This result is not due to phonological priming because phonologically similar primes had no effect on n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
56
4

Year Published

2000
2000
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(69 citation statements)
references
References 57 publications
9
56
4
Order By: Relevance
“…Consistent with previous studies (Arguin & Bub, 1995;Neumann & Klotz, 1994), the subliminal primes were found to affect identification of the conscious instruction letter in the repetition priming procedure in both experiments, with shorter RTs when the prime was congruent, as opposed to incongruent, with the instruction. However, the extent of this repetition priming effect was greater in Experiment 1 than Experiment 2, when the lag between the prime and target was shorter (36 ms and 84 ms in Experiment 1 and 2, respectively).…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with previous studies (Arguin & Bub, 1995;Neumann & Klotz, 1994), the subliminal primes were found to affect identification of the conscious instruction letter in the repetition priming procedure in both experiments, with shorter RTs when the prime was congruent, as opposed to incongruent, with the instruction. However, the extent of this repetition priming effect was greater in Experiment 1 than Experiment 2, when the lag between the prime and target was shorter (36 ms and 84 ms in Experiment 1 and 2, respectively).…”
Section: Discussionsupporting
confidence: 90%
“…An identity condition and the traditional unrelated condition were added to form a total of four priming conditions: (1) physically identical (ID) primes (e.g., B±B); (2) SIM primes (e.g., c±C); (3) DIS primes (e.g., a±A), and (4) unrelated primes (e.g., x±T). Based on previous results (Arguin & Bub, 1995;Bowers et al, 1998), it was predicted that DIS primes should produce facilitation in naming but not in alphabetic decision. In contrast, ID and SIM primes should produce facilitation in both alphabetic decision and naming.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Posner and Mitchell (1967) argued that cross-case priming (a±A) constitutes evidence for phonological processing (i.e., the involvement of a name code) because, in cross-case priming, primes and targets have the same name albeit a different visual shape. However, other studies that looked speci®cally for effects of phonetic/acoustic similarity in letter recognition typically failed to ®nd such phonetic/acoustic effects (Arguin & Bub, 1995;Boles & Eveland, 1983;Carrasco, Kinchla, & Figueroa, 1988). Moreover, cross-case priming does not necessarily need to result from overlap in phonological information.…”
mentioning
confidence: 99%
See 2 more Smart Citations